(untitled) (Research, Society and Development, 2024)
The study focuses on the use of Digital Information and Communication Technologies (DICT) in music teaching. Objectives: to analyze the difficulties faced by teachers in relation to the use of digital information and communication technologies in music teaching in basic education and describe their contributions. This is a qualitative, descriptive study that was based on the database in the field of education (WoS, SCOPUS and ERIC). The search limits were defined as publications from 2017 to 2023 in English, Portuguese and Spanish, using the following criteria: articles available in full and with free access. Review articles, case reports, clinical trials, TCC, master’s dissertations, doctoral theses, books, book chapters, works published in annals and articles inconsistent with the theme were excluded. In the search for production, the following descriptors were used: digital technologies and teaching; digital technologies and music; music and training; music and teaching. Results: the challenges faced by teachers in the use of DICT in basic education refer to the need for training and appropriation of pedagogical strategies that optimize their use, whose contributions are anchored in the advancement of knowledge in the theoretical and practical fields. Conclusion: when teachers use DICT in music teaching, they create an environment conducive to learning, participation, exchange of experiences and development of students’ skills by referring to the context permeated by digital culture.